Tren Terkini dan Arah Masa Depan Penelitian Camellia sinensis tentang Manajemen Berat Badan dan Luaran Terkait Obesitas: Tinjauan Dua Puluh Tahun dan Analisis Bibliometrik - Muhammad Amin Nasution; Didi Nurhadi Illian; Hanifa Rifdah Aiman; Muhammad Andry; Cindy Marcelia; Nia Novranda Pertiwi; Syilvi Rinda Sari; Hindri Syahputri (Journal of Pharmaceutical and Sciences, 2026)
Camellia sinensis (tea) is widely consumed and has been extensively investigated for its potential to support weight management, particularly because of the bioactive catechin epigallocatechin-3-gallate (EGCG). We conducted a bibliometric analysis to map the scope, productivity, collaboration patterns, citation impact, and thematic evolution of research on Camellia sinensis and obesity-related outcomes. We retrieved records indexed in Scopus for 2005–2024 using terms for Camellia sinensis, major tea types, and obesity. After excluding non-original publications, we analysed 897 original research articles with VOSviewer (version 1.6.20) and the Biblioshiny R package, including co-occurrence, collaboration, and citation networks. Annual output increased from 21 articles in 2005 to a peak of 80 in 2020. China produced the most publications (n = 182), while the United States achieved the greatest total citation impact. The leading sources were Nutrients, Journal of Nutritional Biochemistry, and Food & Function; the most prolific authors were Wang Y, Liu Z, and Zhang Y; and Anhui Agricultural University was the most productive institution. Keyword analysis identified four interconnected themes: green tea catechins and lipid metabolism, oxidative stress and polyphenols, gut microbiota and thermogenesis, and obesity-related metabolic syndrome. Recent research increasingly emphasises multi-omics, microbiota interactions, and precision nutrition. These bibliometric findings indicate expanding scientific interest in the potential contribution of Camellia sinensis to weight management and obesity-related metabolic health, while underscoring the need for standardised clinical trials, improved EGCG bioavailability, and cautious translation into clinical and policy settings